Development and Experimental Study of a Small-Scale Energy Harvester for Domestic Usage - Muzaffar Abdul Kadir, Ahmad; Norhisyam Abd Rashid, Wan; Saat, Shahrizal; Wafi Ab Aziz, Ab (International Journal of Engineering and Technology, 2018)
Energy harvester is the system which gather energy from the external environment sources such as radio waves, air flow, water flow, solar energy, wind energy and kinetic energy and specially used to power or recharge small electronic devices. One of the biggest potential which can be utilized to generate energy is the water flow in the home water pipes. Instead of letting the water flow through the pipe, a small water turbine is fixed on the pipe to let the water flow through the pipe and at the same time it will generate electricity to charge a battery. This complete system is installed at the water tank on the roof. A battery monitoring system is developed to monitor the performance of the small energy harvester system. The complete system consists of converter, generator and a monitoring system. To determine the state of charge of the 12V lead-acid battery, a monitoring system that manipulate signal from the signal conditioning system which acquire signal from the DC-DC booster will be converted by using Analog-to-Digital Converter (ADC) and then transferred to smartphone through Bluetooth Module to monitor the status of battery.Â